Status of Catalase, Glutathione Peroxidase, Glutathione S-Transferase, and Myeloperoxidase Gene Polymorphisms in Beta-Thalassemia Major Patients to Assess Oxidative Injury and Its Association with Enzyme Activities - Tripathi, Poonam; Agarwal, Sarita; Tewari, Satyendra; Mandal, Kausik (Journal of Pediatric Genetics, 2021)
Beta-thalassemic patients require regular blood transfusion to sustain their life which leads to iron overload and causes oxidative stress. The aim of this study was to investigate the status of variants in genes including GSTM1, GSTT1 (null/present), CT-262 (C > T) and CT-89 (A > T), glutathione peroxidase (GPx), and myeloperoxidase (MPO). The genotype studies were conducted with 200 thalassemia major (TM) patients and 200 healthy controls. Genotyping of GST gene was performed by multiplex polymerase chain reaction (PCR), whereas for CT, GPx and MPO genesvariants PCR- restriction fragment length polymorphism technique used. However, the enzyme activities were measured only in the patients group to assess the association with the genotypes. All enzyme estimations were performed by ELISA. We observed higher frequency of GSTT1 null, CT-89 (A > T), GPx1 198 (C > T) and MPO-463 (G > A) polymorphisms in TM patient than healthy controls. However, CT-262 (C > T) polymorphism was not found to be statistically significantly different between patients and controls. Our results suggest that frequency of null allele of glutathione-S-transferase is significantly high among TM patients. The other alleles CT-89 (A > T), GPx1 198 (C > T), and MPO-463 (G > A) are linked to decreased CT, GPX, and MPO enzyme activities.
Keywords: thalassemia; glutathione-S-transferase; polymorphism; hemoglobin